In situ analysis of the crystallization process of Sb2S3 thin films by Raman scattering and X-ray diffraction. (5th May 2017) - Parize, Romain; Cossuet, Thomas; Chaix-Pluchery, Odette; Roussel, Hervé; Appert, Estelle; Consonni, Vincent
Abstract: Sb2 S3 thin films grown by chemical bath deposition have received increasing interest for its integration into solar cells. However, its crystallization by post-deposition annealing represents a major difficulty owing to its instability at relatively low temperature. We combine in situ Raman scattering at very low laser power with in situ X-ray diffraction over a broad range of annealing temperatures and durations under N2 atmosphere to elucidate its crystallization process on anatase-TiO2 layers. The thermally activated crystallization is found to systematically involve the intermediate formation of a metallic Sb phase and very often of a senarmontite cubic Sb2 O3 phase, both of them vanishing prior to the formation of the stibnite Sb2 S3 phase. Compact and continuous 150 nm-thick Sb2 S3 thin films with no pyramid-shaped clusters on their top surface are crystallized in the range of 240 to 270 °C, namely below the commonly used annealing temperature of 300 °C. Their texture is tunable from (420) and (520) to (020) and (200) planes parallel to the surface by raising the annealing temperature owing to a process of abnormal grain growth. The Sb2 S3 thin films crystallized at the optimal annealing temperature of 270 °C are composed of dense crystallites with a typical size of several tens of nanometers, which is of high interest for their integration into solar cells. Graphical abstract: Highlights: A metallic Sb phase and very often a senarmontite Sb2 O3 phase are formed during the crystallization of the Sb2 S3 phase. Compact and pure Sb2 S3 thin films with large-sized crystallites are formed at the optimal annealing temperature of 270 °C. The texture is tunable by raising the annealing temperature from 240 to 270 °C owing to a process of abnormal grain growth.